Comparison between an objective and a psychophysical method for the evaluation of intraocular light scattering - Barrionuevo, Pablo Alejandro (2012)
In this study we present the comparison of the performance of two systems to measure intraocular scattering. Measurements were made by using a psychophysical system based on a brightness comparison method that provides a glare index and a physical system based on the double-pass technique, which gives an objective scatter index by measuring the optical quality of the eye. Three external diffuser filters that simulated different grades of intraocular scattering were used in subjects with normal vision. The two measured indexes showed a graded rise with increasing level of scattering. The discrimination ability obtained for both systems showed that they were able to distinguish among conditions ranging from normal to early cataracts.